Evaluasi Kualitas Website Mitratel dengan Pendekatan Webqual Dan Importance Performance Analysis - Muhamad Ricky Nursyamsyi; Fabriyan Fandi Dwi Imaniawan (Elkom : Jurnal Elektronika dan Komputer, 2021)
PT. Dayamitra Telekomunikasi or Mitratel is a subsidiary of PT Telkom Indonesia (Persero) Tbk which is engaged in providing telecommunications infrastructure. Mitratel has been in the telecommunications tower business since 2008. To date, Mitratel has managed more than 13,700 telecommunication towers spread throughout Indonesia. The choice of a website as a company's communication medium with the public is the right decision considering that the website can provide information or messages to anyone who wants that information even though they are in different parts of the world. The website built by the company can provide information related to the company's activities that are considered worthy to be known by the public. Through the website, the public can also find out the company in sufficient detail, starting from the profile, vision and mission, history, contacts, and activities carried out by the company. So far, the Mitratel website has never been evaluated, so the authors evaluate using the Webqual method and Importance Performance Analysis. The results obtained indicate that there are still many parts of the Mitratel website that must be improved.